PELAPISAN LISTRIK KHROM PADA PRODUK KUNINGAN INDUSTRI RUMAH TANGGA DI SUMATERA BARAT DENGAN SUMBER ENERGI BATEREI 60 A/12 V - Asfarizal Saad; Nurzal Nurzal (LP2M - Institut Teknologi Padang, 2014)
In West Sumatra, the creation of domestic industrial metal copper, steel, chromium-coated products do not coated by chrome yet, so it is less interested in the community. Electroplating chrome with a simplified method is expected to increase the added value. Electroplating of copper (Cu) and nickel (Ni) to the steel plate is needed before chromium (Cr) coating. It aims to improve the adhesive of steel plate and to brighten the coating. A solution system used is copper sulfate (CuSO4), i = 6.68 A / dm 2 and t = 2 min, nickel sulfate (NiSO4), i = 3.5 A / dm 2 and t = 2 minutes and chromium acid (HCrO3), i = 5.1 A / dm 2 and t = 20 min. The energy source is a 12 volt 60 Ampere battery. The result shows that: a) the average layer thickness is; Cu 8.54 µm, Ni: 6.65 µm, and Cr: 3.23 µm. b) the adhesive of both layers are good, since there’s no cracks when bending 90 o and 180 o C) coating to some products which are made of brass with chrome anode showed a white color and shiny chrome.